Financing of scientific research projects at the University of Defence - Knežević Milena; Trifunović Dragana; Đukić Slobodan (Ekonomija: teorija i praksa)
The financing of scientific research projects is carried out from multiple sources and locations, all with the common goal of improving the state of military education and scientific research in the defense sector. The aim of this paper is to highlight the importance of adequate financial planning for the development of military education and military scientific research. Naturally, the purpose for which financial resources are used is of great and decisive importance for the quality of both military education and scientific research activities. Accordingly, the central hypothesis of the paper is that knowledge and application of project management principles, along with compliance with relevant procedures, regulations, and the chart of accounts, directly influence the efficient utilization of financial resources allocated for scientific research projects at the University of Defence. This, in turn, impacts the overall success and feasibility of the projects. The paper employs a comparative method - specifically, a comparative analysis of the University's expenditures and expenses from 2016 to 2022, categorized by funding sources-as well as content analysis. Using SPSS software, financial data was analyzed with the aim of enhancing the management of scientific research projects at the University of Defence. Based on this, the authors conclude that the application of project management and familiarity with relevant procedures and regulations are of critical importance for project success, as well as for the effective planning and execution of financial resources.